The business of books : booksellers and the English book trade, 1450-1850 - Raven, James, 1959- (Yale University Press, 2007)
In 1450 very few English men or women were personally familiar with a book; but by 1850, the great majority of people daily encountered books, magazines, or newspapers. This text explores the history of this fundamental transformation.